The impact of brand social media marketing on the dynamics of the company’s share value - Fayvishenko, Diana; Cherniavska, Liudmyla; Bondarenko, Iryna; Sashchuk, Tetiana; Sypchenko, Inna; Lebid, Nataliia (Business: Theory and Practice, 2023)
The aim of the study was to determine the impact of brand social media marketing on the dynamics of the company’s share value. Methods of analysis and synthesis were used to determine the features of the implementation of the brand advertising campaign in social media. The economics and statistics analysis were used to analyse the costs of social media marketing (SMM) of the brands of global companies – leaders in market capitalization of shares, as well as to determine the capitalization level. The monographic method is used for a comprehensive and in-depth study of social media marketing, the causal links between the implementation of the advertising campaign and the overall performance of companies. The essence and importance of social media in the promotion of modern brands are studied considering the results of research and practice of global companies. The advantages of social media marketing activities of companies for brand promotion in the context of increasing the company’s value are identified, which include: increasing brand awareness; increasing the level of conversion and increasing the number of potential customers; direct communication with the target audience; coverage of the target audience which is not covered by traditional types of advertising. The dynamics of expenditures on social media marketing of global brands, as well as the dynamics of the cost of market capitalization of global companies were studied. An econometric regression model was developed to determine the quantitative impact of the costs of global brand social media marketing on the market value of shares of global companies. It was found that with an increase of $ 1 billion in spending on brand social media marketing, the cost of market capitalization of companies’ shares increases by an average of $ 1,445,947. Prospects for further research are to find new and increase the effectiveness of existing methods of brand social media marketing in order to maintain a stable competitive position and gain new competitive advantages.